Crystal Chemical Analysis of Nd9.33Si6O26 and Nd8Sr2Si6O26 Apatite Electrolytes Using Aberration-Corrected Scanning Transmission Electron Microscopy and Impedance Spectroscopy - An, Tao (2016)
Lanthanoid silicate apatite solid electrolytes contain one-dimensional channels. These materials display substantial oxygen mobility at temperatures lower than conventional zirconia-based ionic conductors because interstitial oxygen displacements, mediated by Ln cation vacancies, have a lower activation energy. For these nonstoichiometric apatites, crystal structure solutions derived from X-ray and neutron powder diffraction yield the average atomic arrangement, but these techniques also average over local lattice disorders. Large apatite single crystals permit the evaluation of oxygen migration anisotropy using impedance spectroscopy and the correlation of this behavior to atomic scale domain formation or defect cluster aggregation if present. Aberration-corrected scanning transmission electron microscopy, in both high angle annular dark field (HAADF) and bright field (BF) modalities, was applied to characterize the local atomic structure of Nd9.33Si6O26 and Nd8Sr2Si6O26 apatite electrolytes. Quantitative image analysis found the distribution of metal vacancies and dopant metal in apatites to be remarkably homogeneous at the unit cell scale. This is distinct from other oxide electrolytes including fluorites, perovskites, and melilites, where domain and superstructure formation are a consequence of interstitial oxygen incorporation and prescribe the mode of ionic transport. In the present case, the unexpectedly high perfection of silicate apatites arises from the flexible topological response of one-dimensional channels penetrating the structure, which, in turn, allows robust chemical tailoring of these electrolytes.